Scrutinizing Directed Reading Thinking Activity (DRTA) Strategy on Students' Reading Comprehension - Nerim Nerim (Universitas Pendidikan Mandalika, 2020)
The aim of this research was to examine the directed reading thinking activity (DRTA) strategy on students’ reading skills. This research was classified as experimental research applying a quasi-experimental design. This study involved 60 students of second-grade students of SMPN 1 Jonggat. The students were divided into two groups, the experimental and control groups. The experimental group was subjected to DRTA strategy, while the control group was treated using the conventional learning strategy. The data were obtained by using a reading test. The data were analyzed using descriptive and inferential statistics. The data were calculated using SPSS 19.0 for Windows. The descriptive statistic was aimed at finding out the students’ mean score, mode, median, and standard deviation. Hence, the inferential statistic was used to test the research hypothesis using the independent sample t-test. The results of the research showed that the DRTA strategy in teaching reading had a more positive effect than the conventional learning strategy. It was proven that the students’ mean score in the experimental class (78.80) was higher than those in the control group (73.73). In addition, the score of 2-tailed (0.032) was lower than the sig. level 0.05. Therefore, the hypothesis was accepted. It means that the directed reading thinking (DRTA) strategy had a significant effect on students’ reading comprehension.